**Re: Equations & Parenthesis**
Takitia said:

-3x(x-1)=2(x-8)+3

-3x+-3=2x-16+3

-3x+-3=2x-19

-2x 2x

-3=19

I have no idea what I have done wrong

Have you learned about the distributive property yet? If not maybe that's making these problems harder. What the distributive property means is if you have

2(3+6) you do 2*3 + 2*6.

The 2 is distributed.

What if you have negative signs?

Remember that negative * negative = positive.

2(3-6)=2*3-2*6

and here's another one.

2(-3+6) = 2*(-3) + 2 ( 6)

and another, with negative signs everywhere.

-2(-3-6) = (-2)*(-3) + (-2)(-6) = 2*3 + 2*6

Does that help at all?